A randomised determination of the Effect of Fluvastatin and Atorvastatin on top of dual antiplatelet treatment on platelet aggregation after implantation of coronary drug-eluting stents - Wenaweser, Peter; Eshtehardi, Parham; Abrecht, Linda; Zwahlen, Marcel; Schmidlin, Kurt; Windecker, Stephan; Meier, Bernhard; Haeberli, Andre; Hess, Otto M. (Thrombosis and Haemostasis, 2010)
Drug-drug interaction between statins metabolised by cytochrome P450 3A4 and clopidogrel have been claimed to attenuate the inhibitory effect of clopidogrel. However, published data regarding this drug-drug interaction are controversial. We aimed to determine the effect of fluvastatin and atorvastatin on the inhibitory effect of dual anti-platelet therapy with acetylsalicylic acid (ASA) and clopidogrel. One hundred one patients with symptomatic stable coronary artery disease undergoing percutaneous coronary intervention and drug-eluting stent implantation were enrolled in this prospective randomised study. After an interval of two weeks under dual antiplatelet therapy with ASA and clopidogrel, without any lipid-lowering drug, 87 patients were randomised to receive a treatment with either fluvastatin 80 mg daily or atorvastatin 40 mg daily in addition to the dual antiplatelet therapy for one month. Platelet aggregation was assessed using light transmission aggregometry and whole blood impedance platelet aggregometry prior to randomisation and after one month of receiving assigned statin and dual antiplatelet treatment. Platelet function assessment after one month of statin and dual antiplatelet therapy did not show a significant change in platelet aggregation from 1st to 2nd assessment for either statin group. There was also no difference between atorvastatin and fluvastatin treatment arms. In conclusion, neither atorvastatin 40 mg daily nor fluvastatin 80 mg daily administered in combination with standard dual antiplatelet therapy following coronary drug-eluting stent implantation significantly interfere with the antiaggregatory effect of ASA and clopidogrel.
Keywords: Platelet aggregation; coronary stent; thrombosis; fluvastatin; atorvastatin; clopidogrel; acetylsalicylic acid